Motives for public exposure to advertisement through smart phone applications and its purchasing decisions relationship (A research drawn from a Master Degree thesis) - Gatea, Kisaer Jabbr; al-rawi, Bushra Jameel (ALBAHITH ALALAMI, 2020)
Advertisement on smart phone shopping apps are a new way of driving users to satisfy their needs and influence their purchasing decisions, In this way, the research could be aimed to know The role of the relationship between the motivations for audience exposure to shopping apps advertisement and purchasing decisions, In order to achieve the objectives of the research, the researcher adopted the survey method and used the questionnaire and the scale to collect data and information, The researcher chose the "random sample multi stages", The sample size was (475) respondents from Baghdad city center (18 years and above) women and men.